Paratesticular pleomorphic rhabdomyosarcoma in an adult - (:unkn) unknown (My University, 2004)
Rhabdomyosarcoma (RMS) is the commonest variety of soft tissue sarcoma in children and young adults. It represents 6.5% of all malignant tumours in paediatrics with an annual incidence of 4 to 7 cases/million children. The primary paratesticular site is considered to have a good prognosis in comparison with other rhabdomyosarcomas, despite the frequency of retroperitoneal lymph node invasion. This superficial site allows rapid diagnosis and consequently often complete resection of the tumor. The multi- disciplinary treatment of paratesticular RMS has improved control of the disease with a 2-year survival of 80%. We herein report a case with paratesticular pleomorphic RMS, a rare and prognostically unfavorable variant of RMS, who is disease free for 60 months after management with multidisciplinary approach. © 2004 Kluwer Academic Publishers.
Keywords: Multidisciplinary approach; Paratesticular rhabdomyosarcoma; Poor prognosis